Poly(L-lactic acid) membranes : abscense of genotoxic hazard and potential for drug delivery - Uzun Junior, Nelson (2015)
Biomaterial is defined as any substance from natural sources or synthetic, that can be used in biological tissues without causing deleterious reactions to the body. Widely used for more than four decades, the titanium has an important role in various areas of health. Its use cannot be considered completely safe. The literature reports the presence of atrophy or bone deformation when this material is used for the treatment of fractures or rehabilitation in young patients, in addition to interfering in some imaging tests and uncomfortable to touch. The absorbable polymers, in particular the PLA, are materials with the advantage of being completely absorbed by the body. Although the use of PLA as material for bone synthesis is known, research with the purpose of better understanding the behavior of this polymer front to biological tissue are necessary, because it has different physical and chemical characteristics of titanium, so that you can offer advantages in relation to the metal. These in vitro studies evaluated the behavior of titanium and the PLA at the cellular level and molecular. No cytotoxic effect or genotoxic was observed in the tests with the cells 3T3 and CHO-K1. In addition to replication and gene expression remained unchanged in both experiments with titanium as with the PLA. The latter also showed the ability to incorporate and release molecules.